Effects in the Near‐Magnetopause Magnetosheath Elicited by Large‐Amplitude Alfvénic Fluctuations Terminating in a Field and Flow Discontinuity. Issue 11 (8th November 2018) - Farrugia, C. J.; Cohen, I. J.; Vasquez, B. J.; Lugaz, N.; Alm, L.; Torbert, R. B.; Argall, M. R.; Paulson, K.; Lavraud, B.; Gershman, D. J.; Gratton, F. T.; Matsui, H.; et al.
Abstract: In this paper we report on a sequence of large‐amplitude Alfvénic fluctuations terminating in a field and flow discontinuity and their effects on electromagnetic fields and plasmas in the near‐magnetopause magnetosheath. An arc‐polarized structure in the magnetic field was observed by the Time History of Events and Macroscale Interactions during Substorms‐C in the solar wind, indicative of nonlinear Alfvén waves. It ends with a combined tangential discontinuity/vortex sheet, which is strongly inclined to the ecliptic plane and at which there is a sharp rise in the density and a drop in temperature. Several effects resulting from this structure were observed by the Magnetospheric Multiscale spacecraft in the magnetosheath close to the subsolar point (11:30 magnetic local time) and somewhat south of the geomagnetic equator (−33° magnetic latitude): (i) kinetic Alfvén waves; (ii) a peaking of the electric and magnetic field strengths where E ·J becomes strong and negative (−1 nW/m 3 ) just prior to an abrupt dropout of the fields; (iii) evolution in the pitch angle distribution of energetic (a few tens of kilo‐electron‐volts) ions (H +, He n +, and O n + ) and electrons inside a high‐density region, which we attribute to gyrosounding of the tangential discontinuity/vortex sheet structure passing by the spacecraft; (iv) field‐aligned acceleration of ions and electrons that could be associated with localized magnetosheath reconnection inside the high‐density region; and (v) variable and strong flow changes, which we argue to be unrelated to reconnection at partial magnetopause crossings and likely result from deflections of magnetosheath flow by a locally deformed, oscillating magnetopause. Key Points: We examine effects at MMS in inner magnetosheath of an arc‐polarized structure and a combination of a tangential discontinuity and vortex sheet One effect is that kinetic Alfvén waves are observed by the MMS spacecraft Accelerated plasma flows are seen which are likely due to magnetopause motions resulting from tangential stresses